Предмет: Алгебра,
автор: 89871371408
Решите пожалуйста, алгебра 7класс
Приложения:
Ответы
Автор ответа:
0
a^2 * x - a^2 * y + b^2 * x + c^2 * y - b^2 * y - x*c^2 =
=x(a^2+b^2-c^2)+y(-a^2-b^2+c^2)= -17/5(6^2+6^2-6^2)+8/5(-6^2-6^2+6^2)=
= -17/5 * 36 + -8/5 * 36 = 36 * (-17/5-8/5) = 36 * (-25/5) = 36 * (-5) = -180
=x(a^2+b^2-c^2)+y(-a^2-b^2+c^2)= -17/5(6^2+6^2-6^2)+8/5(-6^2-6^2+6^2)=
= -17/5 * 36 + -8/5 * 36 = 36 * (-17/5-8/5) = 36 * (-25/5) = 36 * (-5) = -180
Автор ответа:
0
Ответ в приложенном фото
Приложения:
Похожие вопросы
Предмет: Химия,
автор: lidaon2304
Предмет: Английский язык,
автор: Аноним
Предмет: Українська мова,
автор: javermix7
Предмет: Математика,
автор: химикданил